ХУДОЖЕСТВЕННАЯ КОНЦЕПЦИЯ КАТЕГОРИИ ПАМЯТИ В ПОВЕСТИ ВАЛЕНТИНА РАСПУТИНА «ПРОЩАНИЕ С МАТЕРОЙ» - Алламуратова, Г.Ж.; Алламуратова, А.Ж. (SCIENCE and SOCIETY, 2022)
The article deals with the internal ethical conflict, which is the starting point of the entire artistic system of the story «Farewell to Matyora», its moral and philosophical concept. It is expressed in the form of a struggle between memory and unconsciousness and has a universal meaning. Memory is being considered as an artistic category, which is consistently expressed in the system of images of this story.